Strategy Modeling to improve Organizational competitiveness Sustainability (A reformulation of the model for implementation) - Muhammad Hidayat (SEIKO : Journal of Management & Business, 2022)
Abstrak Purpose: The current study aims to analyze response of the state-owned company of shipping service sector in adjusting the antitrust law and their implementation of the objectives of the law in increasing the competitiveness of companies through value creation strategies and the distribution of the value throughout company’s branches. Research design, data and methodology: This study was conducted using a qualitative approach to analyze the value formation model carried out by the company and compare the value formation models that have been proposed by experts and previous studies. The current research was conducted in Office Centre of Pos Indonesia and its main branches to find out the Distribution of Value Creation Strategy settled by the Company. All data was analyzed by using data analysis techniques in qualitative approach. Results: The results of this study indicate that the value creation model that has been implemented by the company has referred to the existing value creation models before by adding specific new factors so that the model can be internalized properly and is able to lead the company to take a role in a very dynamic competition in the delivery service sector in Indonesia Kata Kunci: Anti Monopoly, Value Creation, Value Distribution, Competitiveness